Target‐Mediated Drug Disposition Pharmacokinetic/Pharmacodynamic Model‐Informed Dose Selection for the First‐in‐Human Study of AVB‐S6‐500 - Laura Bonifacio; Michael Dodds; David Prohaska; Aaron Moss; Amato Giaccia; Ray Tabibiazar; Gail McIntyre (Wiley, 2020)
AVB‐S6‐500 neutralized growth arrest‐specific 6 (GAS6) protein and effectively inhibited AXL signaling in preclinical cancer models. A target‐mediated drug disposition (TMDD) pharmacokinetic/pharmacodynamic (PK/PD) model was used to select first‐in‐human (FIH) doses for AVB‐S6‐500 based on predicted target (GAS6) suppression in the clinic. The effect of TMDD on AVB‐S6‐500 clearance was incorporated into a standard two‐compartment model, providing parallel linear and nonlinear clearance. Observed AVB‐S6‐500 and GAS6 concentration data in cynomolgus monkeys and relevant interspecies differences were used to predict the PK (serum concentration)/PD (GAS6 suppression) relationship in humans. Human exposure and GAS6 suppression were simulated for the proposed FIH doses of 1, 2.5, 5, and 10 mg/kg. A dose of 1 mg/kg was selected to target GAS6 suppression for 2 weeks in the initial healthy volunteer study. The cynomolgus monkey:human ratios for the highest proposed FIH dose were anticipated to yield more than a 10‐fold margin to the nonclinical no observed adverse event level while maintaining > 90% GAS6 suppression. In human subjects, the first dose (1 mg/kg) model‐projected and clinically observed maximal concentration (Cmax) was within 10% of predicted; repeat dosing at 5 mg/kg was within 1% (Cmax) and 45% (area under the serum concentration‐time curve from time 0 to end of dosing interval) of predicted. Predicted GAS6 suppression duration of 14 days was accurate for the 1 mg/kg dose. A PK/PD model expedited clinical development of AVB‐S6‐500, minimized exposure of patients with cancer to subtherapeutic doses, and rationally guided the optimal dosing in patients.